2017
DOI: 10.1103/physrevb.95.020403
|View full text |Cite
|
Sign up to set email alerts
|

Absence of nematic ordering transition in a diamond lattice: Application toFeSc2S4

Abstract: Recent neutron scattering observations by Plumb et al. [1] reveal that the ground state of FeSc2S4 is magnetic with two distinct Fe environments, instead of a quantum spin liquid as had been previously thought. Starting with the relevant O(N )-symmetric vector model of FeSc2S4, we study how the discrete (Z2) and continuous rotational symmetries are successively broken, yielding nematic and ordered phases. At high temperatures, we find that the nematic order parameter falls as T −γ (γ > 0), and therefore, FeSc2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As a very new research direction, drumhead state measurements have already been demonstrated in a photonics setting [34]. Furthermore, quasiparticle interference measurements appear highly promising for mapping out the drumhead states [70,87]. This technique was already employed to map the Fermi arcs of nodal points [71].…”
Section: Possible Reconstruction Of Nodal Loop Linkage From Momentmentioning
confidence: 99%
“…As a very new research direction, drumhead state measurements have already been demonstrated in a photonics setting [34]. Furthermore, quasiparticle interference measurements appear highly promising for mapping out the drumhead states [70,87]. This technique was already employed to map the Fermi arcs of nodal points [71].…”
Section: Possible Reconstruction Of Nodal Loop Linkage From Momentmentioning
confidence: 99%
“…Previously, the single impurity effects have been widely used to investigate physical properties such as the pairing symmetry in various unconventional superconductors [38,[40][41][42]. They have also been studied intensively in various topologically nontrivial systems, including several topological superconductor/superfluid systems [43][44][45][46][47][48][49][50][51], topological insulators [52,53], and topological Weyl semimetals [54]. The NLS is a relatively new member to topological materials.…”
Section: Introductionmentioning
confidence: 99%
“…The NLS is a relatively new member to topological materials. Previously the quasiparticle interference in the normal and superconducting NLS was studied theoretically [51]. And the possible resonant state of the NLS with the d-wave superconducting order was also discussed [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the fairly weak SOC in this system precludes the exchange frustration scenario. Furthermore, while the subtle interplay between the SOC and the e g orbital manifold may produce a unique spin-orbital entangled singlet state and thereby result in spin-liquid-like behavior in some Fe 2+ -based systems [28][29][30][31][32], it is unlikely to occur in CFTO due to distinct crystal field environments and orbital characters (see below for details).…”
mentioning
confidence: 99%